PERBANDINGAN NPL, LDR, CAR, ROA, DAN BOPO ANTARA BANK BNI DAN BANK BUMN LAIN - Tri Wahyuningsih; Fifi Swandari (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
This study aims to analyze the differences in financial performance of Bank BNI and other BUMN Banks by the measuring the ratio of Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Adecuacy Capital Ratio (CAR), Return on Assets (ROA) and BOPO. The study was conducted by using descriptive analysis method. The results of this study explained that the performance NPL, LDR, and Bank BNI’s CAR on average during the past eight semesters was still better than BUMN Banks on average, while the performance of ROA and BOPO remained below the average Revenues and Operating Expenses of Operational Income of Bank BUMN. The results also showed that all BUMN banks still showed good and healthy performance and in accordance with the provisions set by Bank Indonesia. This study also presented the strategy undertaken by Bank BNI to improve its financial performance, that is, the business synergy of all units unit, growth in goodquality assets, optimization of the customer engagement, strengthening the network and develop alliances, optimization of existing resources and simplification of processes, and enhancing customer experiences through improving processes and business models to digital banking